WEBINAR TRAINING OF EARLY DETECTION OF CONGENITAL HEART DISEASE FOLLOWED BY ECHOCARDIOGRAPHY AND PULSE OXIMETRY SCREENING IN LUMAJANG, EAST JAVA, INDONESIA - Mahrus Abdur Rahman; I Ketut Alit Utamayasa; Teddy Ontoseno; Taufiq Hidayat; Henry Wicaksono (Jurnal Pengabdian Kesehatan Masyarakat, 2022)
Congenital heart disease (CHD) affects about 0.8% to 1.2% with the mortality rate being 81 cases per 100,000 live births. Generally, CHD is a structural abnormality of the heart and (or) large blood vessels that appear at birth. The purpose of this activity is to conduct webinar training on early detection of congenital heart disease followed by ecocardiography and oximetry pulse screening in lumajang east Java Indonesia the novelty in this service activity because it provides training on early detection of heart disease. The training method was carried out through webinars with health worker participants in Lumajang. The material provided includes early detection methods, diagnosis and therapy, as well as simulations of CHD cases. Pre and Post-test are used to evaluate the level of knowledge. A visit to the echocardiography and pulse oximetry examination by a pediatric cardiologist was carried out two weeks later in Lumajang. As a result of the activity, there were 140 participants who took part in the webinar training. The average score of the pre-test was 11.13/15 with only 5 participants getting a perfect score. At the end of the webinar, the average post-test score was 14.34/15 with 115 participants who finally got a perfect score. A total of 28 children were examined by echocardiography examination. 20 children were diagnosed with cyanotic CHD, 6 children were diagnosed with cyanotic CHD, and 2 were normal children. On pulse oximetry examination, all babies had an oxygen saturation of 95% or more and there was no difference of more than 3% between the pre and post duct sites. Conclusion Webinar training can increase health workers' knowledge about early detection of CHD.Keywords : Congenital Heart Disease; Filtering; Echocardiography; Pulse oximetry.